Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/eat.22951
|View full text |Cite
|
Sign up to set email alerts
|

Warning labels on fashion images: Short‐ and longer‐term effects on body dissatisfaction, eating disorder symptoms, and eating behavior

Abstract: Objective: Fashion warning labels that caution readers about digitally altered images have been recommended and adopted by several countries to prevent body dissatisfaction and eating disorders. This study investigated the short- and longer-term influence of fashion warning labels on affect, body dissatisfaction, eating disorder symptoms, and snack consumption using a randomized-controlled experiment. Method: Female undergraduates (n = 118) were randomized to view and rate responses to fashion images either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…For example, as part of a strategic science approach, it has been proposed that researchers partner with government influencers to develop research questions that address the impacts of policy decisions (Roberto & Brownell, ) and consider questions important in health financing decisions, such as whether there is a need for greater regulation (Whiteford & Weissman, ). There are numerous potential system reforms that require examination, such as the influence of private and public health insurance (Escobar‐Koch et al, ), media, and advertising regulation (Kwan, Haynos, Blomquist, & Roberto, ), standardized evaluation of services (Attia, Marcus, Walsh, & Guarda, ), and training and accreditation standards (Whiteford & Weissman, ). Although it is expected that such reforms will have advantages in addressing barriers to treatment access, there are likely to be challenges in measuring their effects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as part of a strategic science approach, it has been proposed that researchers partner with government influencers to develop research questions that address the impacts of policy decisions (Roberto & Brownell, ) and consider questions important in health financing decisions, such as whether there is a need for greater regulation (Whiteford & Weissman, ). There are numerous potential system reforms that require examination, such as the influence of private and public health insurance (Escobar‐Koch et al, ), media, and advertising regulation (Kwan, Haynos, Blomquist, & Roberto, ), standardized evaluation of services (Attia, Marcus, Walsh, & Guarda, ), and training and accreditation standards (Whiteford & Weissman, ). Although it is expected that such reforms will have advantages in addressing barriers to treatment access, there are likely to be challenges in measuring their effects.…”
Section: Introductionmentioning
confidence: 99%
“…Limiting the modification of images is a frequently recommended policy avenue for reducing DWCB risk among populations, but several articles in this review described that warning labels on altered images may unintentionally trigger greater body image concern (Danthinne et al, 2020; Giorgianni et al, 2020; Kwan et al, 2018; McBride et al, 2019; Paraskeva et al, 2017). One older study found that viewing warning labels resulted in reduced body dissatisfaction (Slater et al, 2012), but this finding was rare in a systematic review and meta‐analysis of studies investigating the impact of disclaimer or warning labels on body image (Danthinne et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To pursuit the so-called ideal bodies, some women engage in unhealthy dieting and other compensatory behaviors such as excessive exercises [45,46] . Beyond such short-term effects on women, several studies indicate that the self-objectification of women can also exert long-term impacts on personal growth and career development [6,47] . As an example, Wang et al randomly assigned participants to the high-or low-competitive condition, then asked them to report state self-objectification and the belief of personal growth (measuring to what extent participants believed they could live productive, fulfilling, and meaningful lives) [6] .…”
Section: Visual Wealth Exposure On Social Media Female Self-objectifi...mentioning
confidence: 99%